Analisis Kepuasan Kerja Pegawai Di Kantor Inspektorat Kabupaten Mandailing Natal - Novaal Novita; Ade Fay Eve; Angellina Joel (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
The purpose of this study was to determine the level of job satisfaction of employees at the Mandailing Natal District Inspectorate Office. To obtain the expected analysis results, in this study a descriptive method was used through a quantitative approach and then verified. From the results of data analysis and discussion, it was concluded that the job satisfaction level category of the Mandailing Natal District Inspectorate employee was "Satisfied" with an average score of respondents' answers of 3.6. Of all the existing indicators it can be concluded that the highest score was obtained by the third indicator, namely working conditions with an average score of 3.8. This means that the working conditions in the Mandailing Natal District Inspectorate support a good work climate so that employees feel this gives them job satisfaction. Whereas the lowest score was obtained on the first indicator, namely salary with an average score of 3.4. This low score is important to be discussed by the Mandailing Natal District Inspectorate because salary is the main thing for someone to do work. Of the 7 (seven) indicators used to measure job satisfaction of the Mandailing Natal District Inspectorate employees, an average score was obtained, namely the first indicator obtained an average score of 3.4 (satisfied), the second and fourth indicators obtained an average score of equal to 3.6 (satisfied), the third indicator obtained an average score of 3.8. This score is also included in the satisfied category. In the fifth and seventh indicators, the average score is equal to 3.7 (satisfied). And the sixth indicator obtained an average score of 3.5 (satisfied).